2020
DOI: 10.1002/brb3.1720
|View full text |Cite
|
Sign up to set email alerts
|

Altered white matter integrity in patients with monocular blindness: A diffusion tensor imaging and tract‐based spatial statistics study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…We analyzed the average values of FA and RD through the ROC methods as previously described [ 20 ]. The area under the curve (AUC) represented the diagnostic rate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed the average values of FA and RD through the ROC methods as previously described [ 20 ]. The area under the curve (AUC) represented the diagnostic rate.…”
Section: Methodsmentioning
confidence: 99%
“…A TBSS analysis of patients with concomitant exotropia showed that FA increased and RD decreased in the relevant areas [ 18 ]. TBSS was applied to investigate the white matter integrity of patients with congenital and terminal blind and monocular blindness and found the different mechanisms of structural changes in white matter [ 19 , 20 ]. Therefore, our purpose here is to use TBSS analysis to research the alterations and to explore the diffusivities of fiber bundles in RVO patients.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional MRI studies provide valuable qualitative insights into myopia and posterior staphyloma based on objective and quantitative measurements ( Guo et al, 2017 ). Visual deprivation can cause abnormal function of the visual cortex and vision-related cortex, and lead to plastic changes in the brain’s visual system ( Liu et al, 2020 ). Using the VBM method, Takeuchi ( Takeuchi et al, 2018 ) found that refractive errors appear to be mainly associated with the volume of the cranium.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Li et al (2012) reported an increased concentration of WM in patients with high myopia, primarily in the calcarine area and the prefrontal and parietal lobes. Meanwhile, Liu discovered abnormal spontaneous alterations in WM of monocular blindness patients ( Liu et al, 2020 ). However, there is currently limited research on brain morphology regarding myopia onset during the sensitive period of development.…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion tensor imaging (DTI) is a noninvasive imaging method to exhibit the continuity and integrity of tissue structure of living tissue based on two parameters fractional anisotropy (FA) and apparent diffusion coefficient (ADC) [ 10 ]. DTI’s ability to in vivo anatomical evaluation of injury-dysfunction relationships [ 11 , 12 ] makes it successful to assess PA-induced visual pathway damage [ 13 ] by reflecting the microstructural changes of the optic nerve, optic chiasma, optic tract, and optic radiation.…”
Section: Introductionmentioning
confidence: 99%